Export of Strongly Diluted Greenland Meltwater From a Major Glacial Fjord. Issue 9 (5th May 2018) - Beaird, Nicholas L.; Straneo, Fiammetta; Jenkins, William
Abstract: The Greenland Ice Sheet has been, and will continue, losing mass at an accelerating rate. The influence of this anomalous meltwater discharge on the regional and large‐scale ocean could be considerable but remains poorly understood. This uncertainty is in part a consequence of challenges in observing water mass transformation and meltwater spreading in coastal Greenland. Here we use tracer observations that enable unprecedented quantification of the export, mixing, and vertical distribution of meltwaters leaving one of Greenland's major glacial fjords. We find that the primarily subsurface meltwater input results in the upwelling of the deep fjord waters and an export of a meltwater/deepwater mixture that is 30 times larger than the initial meltwater release. Using these tracer data, the vertical structure of Greenland's summer meltwater export is defined for the first time showing that half the meltwater export occurs below 65 m. Plain Language Summary: The Greenland Ice Sheet has been melting at an accelerating pace. As it melts, more and more freshwater drains into the Northern North Atlantic. This may have significant impacts on ocean circulation. In order to start to understand these impacts, we need better observations of the spreading of ice sheet meltwater around coastal Greenland. In this work we use noble gases as a natural "dye" that traces out the pathways of ice melt in coastal waters. These "dyes" give us a powerful tool to measure the size and location of ice melt export. This paper quantifies the flux of two types of meltwater in a major East Greenland fjord and shows that the meltwater is highly diluted by mixing with warm, salty waters from the deepest part of the fjord. Showing which ocean waters dilute the glacial melt is one step toward better representing these processes in numerical models. Key Points: Direct observations of meltwater export from a major Greenland glacial fjord are reported Properties of the exported meltwater mixture are dominated by entrainment and upwelling Noble gases reveal the vertical structure of Greenland meltwater forcing of the coastal ocean